(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Diabetes is one of the most leading cause of death worldwide. Around 40 million diabetics are reported in India. Stem cell therapy is a branch of medicine that involves introducing stem cells into a diseased tissue which triggers the body’s ability to heal itself. Stem cell therapy is a latest technique which can be used to treat diabetes mellitus. In India the success rate of stem cell therapy in diabetes mellitus is approximately 70 - 80 %. As this stem cells may be harvested from the bone marrow, umbilical cord and matured adult. In the present review we are discussing about the use of stem cell therapy in type 2 diabetes and how it works. Type 2 diabetes mellitus results from combination of insulin resistance and dysfunction of insulin producing beta cells which cannot be reversed by existing therapeutic strategies, transplantation of stem cells which are differentiating into insulin producing cells is one of the most promising strategy for treating type 2 diabetes.